Research on target assignment method based on ant colony-fish group algorithm. (December 2019) - Jiang, Haobo; Li, Song; Lin, Chi; Wang, Chuang; Tian, Guilin; Wang, Siyuan; Zhong, Kaiqi; Li, Jiakun
Abstract: Target assignment problem has always been the focus of scholars. The solution of target problem belongs to classical mathematical problem. This paper combines ant colony algorithm with artificial fish swarm algorithm by understanding intelligent algorithm. The concept of crowding degree is introduced into fish swarm algorithm. In the early stage of the algorithm, the dispersion is large, avoiding premature maturity. In the later stage, the convergence speed of the algorithm is faster and the time is saved. Compared with other algorithms, the hybrid algorithm has the characteristics of strong optimization ability and fast speed.